A pH-Responsive Charge-Reversal Drug Delivery System with Tumor-Specific Drug Release and ROS Generation for Cancer Therapy - Xu C (Dove Medical Press, 2020)
Chen Xu,1,2,* Rijin Song,1,* Pei Lu,1,* Jianchun Chen,2 Yongqiang Zhou,2 Gang Shen,2 Minjun Jiang,2 Wei Zhang1 1Department of Urology, The First Affiliated Hospital of Nanjing Medical University, Nanjing 210029, People’s Republic of China; 2Department of Urology, Affiliated Wujiang Hospital of Nantong Univerisity, Suzhou 215200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Zhang Email weizhangsir@126.comMinjun Jiang Email 463161688@qq.comIntroduction: Poor cell uptake and incomplete intracellular drug release are the two major challenges for polymeric prodrug-based drug delivery systems (PPDDSs) in cancer treatment.Methods: Herein, a PPDDS with pH-induced surface charge-reversal and reactive oxygen species (ROS) amplification for ROS-triggered self-accelerating drug release was developed, which was formed by encapsulating a ROS generation agent (vitamin K3 (VK3)) in pH/ROS dual-sensitive polymetric prodrug (PEG-b-P(LL-g-TK-PTX)-(LL-g-DMA)) based micelle nanoparticles (denoted as PVD-NPs).Results: The surface charge of the PVD-NPs can change from negative to positive for enhanced cell uptake in response to tumor extracellular acidity pH. After internalization by cancer cells, PVD-NPs demonstrate dual drug release in response to intracellular ROS-rich conditions. In addition, the released VK3 can produce ROS under the catalysis by NAD(P)H:quinone oxidoreductase-1, which facilitates tumor-specific ROS amplification and drug release selectively in cancer cells to enhance chemotherapy.Conclusion: Both in vitro and in vivo experiments demonstrated that the PVD-NPs showed significant antitumor activity in human prostate cancer.Keywords: charge-reversal, dual-responsive, ROS generation, cancer specific chemotherapy